Upaya Pemberdayaan Petani Kelapa (Cocos Nucifera) di Desa Pesaban, Kecamatan Rendang, Kabupaten Karangasem - NI KOMANG TRI ASTRINI; I MADE SARJANA; I GEDE SETIAWAN ADI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Coconut Farmers Empowerment Effort (Cocos Nucifera) in the Village of Pesaban,Sub-District of Rendang, Regency of Karangasem. Pesaban Village, Rendang Sub-District of Karangasem Regency has great coconutpotential, but farmers can’t utilize the condition properly. The purpose of this researchis to investigate: (1) coconut farming potential, (2) aspect and effort of empowering thecoconut farmers. The research uses qualitative and quantitative analysis methods. Theresults showed that the potential of natural resources of coconut farming, humanresources, and financial resources are good. Ownership of assets is good and belongs tothe farmers themselves, relationships between individuals and groups are wellestablished, coconut farmers have organizations to cooperate, and the partnershipsynergy of coconut farmers with the local and outside traders. Access to information isvery less, the participation of the group has been well built, coconut farmers have asense of responsibility in maintaining the good quality of the product, group forumshave not fully be a problem-solving.